The effects of digoxin on heart failure mortality and re-admission in a single center cross-sectional study - Mahsa Behnemoon; Zahra Borumandkia (Journal of Cardiovascular and Thoracic Research)
Introduction: Mortality benefit of digoxin prescription in patients suffering from heart failure has been questioned many time. We evaluated these effects among admitted symptomatic heart failure patients. Methods: We retrospectively divided our patients into two groups: group A (n=205) were digoxin prescribed, and group B (n=96) were digoxin naïve patients. Both groups’ medical records were gathered for one year, and the study endpoints were compared between the two groups. Results: The mean age was 62.3±12.1 years and 54.8 % were male. All-cause mortality and readmission occurred in 26.7% and 31.7% of individuals, respectively, without significant differences between the two groups. However, in subgroup analysis, there was a significant relationship between in-hospital mortality and the presence of cardiovascular risk factors. Conclusion: Digoxin might increase in-hospital mortality in patients with underlying cardiovascular risk factors.